Risk factors for bronchial asthma in children in Chita Region - I. N. Gaimolenko; N. L. Potapova (Бюллетень сибирской медицины, 2007)
Risk factors for bronchial asthma in children of Chita Region were studied. According to the literature data, 12 clinical-anamnestic characteristics were suggested to be risk factors for bronchial asthma. Prevalence of risk factors was assessed in 72 children with severe asthma, 60 children with moderate, and 58 children with mild bronchial asthma. Odds ratios (OR) with the 95% confident interval for each factor were calculated. Factors with predominance in the asthma group included: parental history of asthma (OR = 16.2), congenital abnormalities and complications of pregnancy and labor (OR = 1.9), prenatal lesion of central nervous system (OR = 2.8), recurrent respiratory tract infections (OR = 12.4), coexisting atopic dermatitis (OR = 1.8), passive smoking (OR = 2.8), and food sensitization (OR = 7.7). The findings can be used to calculate individual risks in a population for prediction of development of this pathology and for its timely prevention.